ANALISIS KUALITAS PELAYANAN SURAT IJIN MENGEMUDI (SIM) PADA SATUAN PENYELENGGARA ADMINISTRASI SIM (SATPAS) POLRESTABES SEMARANG - Reifandi Yusuf Pratama; Ida Hayu Dwimawanti; Tri Yuniningsih (Journal of Public Policy and Management Review, 2023)
The aim of this research is to analyze the quality of SIM services at the Semarang Police SIM Administration Unit. The Semarang Police Driver's License Administration Unit (SATPAS) is an implementing element tasked with carrying out police duties including guarding, regulating, escorting, patrolling, community education and traffic engineering as well as carrying out activities such as registration and removal of motor vehicle drivers, investigating traffic accidents and carrying out enforcement. law in the field of traffic. Researchers use primary data obtained, either through direct observation or questions asked directly to respondents. The research method used was a qualitative descriptive research method and the selection of informants used a purposive sampling technique. Data collection techniques through interviews, direct observation and documentation. There were 11 informants in this study. The research results show that service is still not satisfactory. The service quality indicators used are Tangible, Reliability, Responsiveness, Assurance, Emphaty. Researchers provide recommendations for providing antiintermediary services outreach to the community, providing guidance to officers so that honest, good and competent individuals are formed. Apart from that, additional officers are needed to optimize services to the community